2016
DOI: 10.1086/688084
|View full text |Cite
|
Sign up to set email alerts
|

An International Physician Survey of Chronic Thromboembolic Pulmonary Hypertension Management

Abstract: Abstract:We conducted an international study to evaluate practices in the diagnosis and management of patients with chronic thromboembolic pulmonary hypertension (CTEPH) globally across different regions. Between August and October 2012, CTEPH-treating physicians completed a 15-minute online questionnaire and provided patient record data for their 2-5 most recent patients with CTEPH. Overall, 496 physicians (Europe: 260; United States: 152; Argentina: 52; Japan: 32) completed the questionnaire and provided pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 12 publications
2
43
1
1
Order By: Relevance
“…GALL et al [41] recently reported the findings of an international physician survey of CTEPH management practice, in which it was found that a relatively higher proportion of patients in Europe than the USA (43% versus 12%) were diagnosed with CTEPH in pulmonary hypertension expert centres. In addition, the use of V′/Q′ scanning in the diagnosis of CTEPH was very low (40% and 45% in pulmonary hypertension centres in Europe and the USA, respectively), contrary to guideline recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…GALL et al [41] recently reported the findings of an international physician survey of CTEPH management practice, in which it was found that a relatively higher proportion of patients in Europe than the USA (43% versus 12%) were diagnosed with CTEPH in pulmonary hypertension expert centres. In addition, the use of V′/Q′ scanning in the diagnosis of CTEPH was very low (40% and 45% in pulmonary hypertension centres in Europe and the USA, respectively), contrary to guideline recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…There appeared to be regional variations in the numbers of patients in NYHA FC III/IV at diagnosis in this study, particularly between Japan and Europe. An international physician survey of CTEPH diagnosis and management practice showed that the majority of patients were in WHO FC III/IV at diagnosis, with some variation in WHO FC between the regions assessed (which included Europe, the USA and Japan) [41]. The reasons for these regional differences are unclear, but may relate to levels of awareness of CTEPH in different regions, which could then impact on likelihood of earlier diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations